2009
DOI: 10.1590/s1413-86702009000300002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing of methicillin-resistant Staphylococcus aureus (MRSA) strains isolated in two metropolitan areas of São Paulo State, southeast Brazil

Abstract: One hundred and fifty-one methicillin-resistant Staphylococcus aureus (MRSA) strains have been isolated from patients admitted in tertiary care hospitals in two metropolitan areas (Campinas City and Ribeirão Preto City) in the southeast region of Brazil and analyzed through PCR-based techniques [(PCR amplification of spa, coa, and housekeeping genes (arcC, aroE, gmk, pta, tpi, yqiL)] and further restriction fragment typing of coa and of housekeeping genes. The heterogeneity of spa gene was determined directly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
4
1
2
Order By: Relevance
“…Three standard MRSA strains were also used in this work. The strains MRSA N315 [23], BEC9393 [24] and rib1 [25] were provided by Dr. Elsa Masae Mamizuka (Universidade de São Paulo, São Paulo-SP, Brazil), Dr. Agnes Marie Sá Figueiredo (Universidade Federal do Rio de Janeiro, Rio de Janeiro-RJ, Brazil), and Dr. Wanderley Dias da Silveira (Universidade Estadual de Campinas, Campinas-SP, Brazil), respectively. All strains were stored at - 80°C in stocks containing glycerol (2.5 M).…”
Section: Methodsmentioning
confidence: 99%
“…Three standard MRSA strains were also used in this work. The strains MRSA N315 [23], BEC9393 [24] and rib1 [25] were provided by Dr. Elsa Masae Mamizuka (Universidade de São Paulo, São Paulo-SP, Brazil), Dr. Agnes Marie Sá Figueiredo (Universidade Federal do Rio de Janeiro, Rio de Janeiro-RJ, Brazil), and Dr. Wanderley Dias da Silveira (Universidade Estadual de Campinas, Campinas-SP, Brazil), respectively. All strains were stored at - 80°C in stocks containing glycerol (2.5 M).…”
Section: Methodsmentioning
confidence: 99%
“…MRSA accounted for 54 % of nosocomial S. aureus infections in Brazil in 2006 [ 9 ]. A multiresistant HA-MRSA clone, known as Brazilian epidemic clone (BEC), characterized as sequence type (ST) 239 and SCC mec III, is responsible for the majority of nosocomial infections in Brazil [ 10 12 ]. However, more recent studies reported a frequent occurrence of the MRSA USA800/Paediatric clone (PC) (ST5-SCC mec IV), USA100/New York/Japan clone (ST5-SCC mec II), USA400 (ST1-SCC mec IV) and USA1100/Southwest pacific clone (SWP) (ST30-SCC mec IV) in Brazilian hospitals [ 13 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Shrestha et al 71 described the nasal carriage of Staphylococcus aureus among health care workers in a Nepal hospital. Cury et al 72 studied 151 methicillin-resistant (MRSA) strains isolated from patients admitted to tertiary care hospitals in two metropolitan areas (Campinas City and Ribeirao Preto) in the southeast of Brazil through PCR-based techniques and found that the variability among such strains is larger than previously reported, indicating that the techniques used by these authors can be an alternative to pulsed-field gel electrophoresis.…”
Section: Methodsmentioning
confidence: 98%